Interleukin-4 inhibits kappa light chain expression and NF kappa B activation but not I kappa B alpha degradation in 70Z/3 murine pre-B cells. - Clarke, C; Taylor-Fishwick, D; Hales, A; Chernajovsky, Y; Sugamura, K; Feldmann, M; Foxwell, B (1995)
The murine pre-B cell line 70Z/3 responds to lipopolysaccharide by up-regulating the surface expression of kappa (kappa) light chain through activation of the transcription factor NF kappa B. Interleukin-4 (IL-4), a T cell cytokine, is a known inhibitor of some LPS-mediated events. We investigated whether IL-4 could inhibit the up-regulation of kappa light chain and activation of NF kappa B by LPS in 70Z/3. IL-4 partially inhibited both the LPS-induced expression of kappa light chain and also the activation of NF kappa B as judged by an NF kappa B reporter gene assay. Additionally, electrophoretic mobility shift assays confirmed this effect on LPS-induced NF kappa B DNA binding activity in the nucleus. Surprisingly, proteolytic degradation of I kappa B alpha (MAD3), a prerequisite for NF kappa B activation, was unaffected by IL-4, implying that this cytokine inhibits some subsequent undefined event in the activation of NF kappa B. IL-4 was also found partially to inhibit NF kappa B activity induced by tumor necrosis factor-alpha (TNF-alpha) and interleukin-1-beta (IL-1 beta). These results indicate that there may be a common mechanism for the well-documented anti-inflammatory effects of IL-4 and that this mechanism involves the transcription factor NF kappa B.